Pengembangan Multimedia Interaktif Berbasis Android pada Materi Shalat Fardhu Kelas VII MTs Izzatul Ma’arif Tappina - Nurhidayahsuaib; Buhaerah; Firman (Universitas Islam Negeri Alauddin Makassar, 2024)
The aims of this study were: (1) To find out the process of developing Android-based interactive learning multimedia on fardhu prayer material in class VII of MTs Izzatul Ma'arif Tappina. (2) To find out whether Android-based interactive multimedia met the valid, practical, and effective criteria for fardhu prayer material in class VII of MTs Izzatul Ma'arif Tappina. This was a research and development adapted from the development model by Thiagarajan, namely the 4D model (define, design, develop and disseminate). The result of this study indicated that the development of android-based interactive learning multimedia on fardhu prayer material had met: (1) Valid criteria. This was based oh product validation by media and material experts with an average value of 3.8 and 3.6. Meanwhile, the result of the small group trial produced an average value of 3.76, and the large one was 3.78; (2) Practical criteria. The observation done by the two observers got an average value of 1.79; (3) Effective criteria. Based on the analysis of learning outcomes test including (a) The Paired Sample T-Test showed a significance value of 0.001, which meant the sig value < 0,05. So, Ho was rejected and Ha was accepted, (b) The N-Gain test showed a gain score of 0,56 which was included in the medium category with testing criteria of 0,7 > (N-Gain) > 0,3. As for the analysis of teacher activity, a score of 91.52% was included in the very good category. Meanwhile, the average student activity was 3.50 categorized as active. Then, the analysis of student response questionnaires obtained an average value of 93%. Keywords: Development, Multimedia, Learning, Interactive, Android, Shalat Fardhu.